A phase Ib study of interleukin-2 plus pembrolizumab for patients with advanced melanoma - Silk, Ann W.; Curti, Brendan; Bryan, Jennifer; Saunders, Tracie; Shih, Weichung; Kane, Michael P.; Hannon, Phoebe; Fountain, Christopher; Felcher, Jessica; Zloza, Andrew; Kaufman, Howard L.; Mehnert, Janice M.; et al. (Frontiers in Oncology, 2023)
High-dose interleukin-2 (HD IL-2) and pembrolizumab are each approved as single agents by the U.S. F.D.A. for the treatment of metastatic melanoma. There is limited data using the agents concurrently. The objectives of this study were to characterize the safety profile of IL-2 in combination with pembrolizumab in patients with unresectable or metastatic melanoma. In this Phase Ib study, patients received pembrolizumab (200 mg IV every 3 weeks) and escalating doses of IL-2 (6,000 or 60,000 or 600,000 IU/kg IV bolus every 8 hours up to 14 doses per cycle) in cohorts of 3 patients. Prior treatment with a PD-1 blocking antibody was allowed. The primary endpoint was the maximum tolerated dose (MTD) of IL-2 when co-administered with pembrolizumab. Ten participants were enrolled, and 9 participants were evaluable for safety and efficacy. The majority of the evaluable participants (8/9) had been treated with PD-1 blocking antibody prior to enrollment. Patients received a median of 42, 22, and 9 doses of IL-2 in the low, intermediate, and high dose cohorts, respectively. Adverse events were more frequent with increasing doses of IL-2. No dose limiting toxicities were observed. The MTD of IL-2 was not reached. One partial response occurred in 9 patients (11%). The responding patient, who had received treatment with an anti-PD-1 prior to study entry, was treated in the HD IL-2 cohort. Although the sample size was small, HD IL-2 therapy in combination with pembrolizumab appears feasible and tolerable.